Prevalence and Social Inequality in Experiences of Domestic Abuse Among Mothers of Young Children: A Study Using National Survey Data from Scotland - Skafida, Valeria (Journal of interpersonal violence, 2022)
Domestic abuse is a pernicious societal issue that has both short- and long-term consequences for those who are victimized. Research points to motherhood being linked to women?s victimization, with pregnancy being a particular point of risk. Across UK jurisdictions, new legislation aims to extend the criminalization of domestic abuse to include coercive control. Less clear is the relationship between mothers? victimization of different ?types? of abuse and other factors such as age, socioeconomic status, and level of education. The article makes an original contribution to knowledge by addressing these limitations of the existing literature. Using nationally representative data from a Scottish longitudinal survey (N = 3,633) into children?s development this article investigates the social stratification of mothers? exposure to different types of abuse, including coercive control, physical abuse, and threats. Overall, 14% of mothers report experiencing any type of domestic abuse since the birth of the study child (age 6), of which 7% experienced physical abuse. Compared to mothers in the highest income households, mothers in the lowest income quintile were far more likely to experience any form of abuse (Logistic Regression, OR = 3.55), more likely to have experienced more types of abuse and to have experienced these more often (OR = 5.54). Age had a protective effect, with mothers aged 20 or younger at most risk of abuse (OR = 2.60 compared to mothers aged 40+). Interaction effects between age and income suggested that an intersectional lens may help explain the cumulative layers of difficulty which young mothers on low incomes may find themselves in when it comes to abusive partners. The pattern of social stratification remained the same when comparing different types of abuse. Mothers of boys were more likely to experience abuse, and to experience more types of abuse, more often. We reflect on how these findings could inform existing policy interventions.